Simultaneous Estimation of Aceclofenac and Paracetamol in Tablet Dosage Form by UV Spectroscopy - JAIN, ANUREKHA; JAIN, AVIJEET; VYAS, VIVEK; SUBEDAR, NIHARIKA; GUPTA, ARUN (Asian Journal of Chemistry, 2010)
A simple, precise, rapid and selective simultaneous equation and Q-analysis UV spectrophotometric method has been developed for the simultaneous determination of aceclofenac and paracetamol from combined tablet dosage form. The method involves solving of simultaneous equation value analysis based on measurement of absorptivity at 276, 249 and 270 nm, respectively. Linearity lies between 2-25 mcg/mL for aceclofenc and 1-30 mcg/mL for paracetomol. Results of analysis for both the method were validated statistically and by recovery studies.